Changes in Pediatric Hospital Care during the COVID‐19 Pandemic: A National Qualitative Study. (15th September 2021) - Penwill, Nicole; De Angulo, Nadia Roessler; Elster, Martha; Pathak, Priya; Ja, Clairissa; Hochreiter, Daniela; Wilson, Karen; Newton, Jacqueline; Kaiser, Sunitha
Abstract : Research Objective: The COVID‐19 pandemic has necessitated rapid changes in healthcare delivery in the United States, including changes in the care of hospitalized children. This study aims to identify major changes in inpatient pediatric healthcare delivery and potential lessons learned. Study Design: In this study, we conducted semi‐structured video interviews. We analyzed interview data using constant comparative methods to identify major healthcare delivery changes for hospitalized children during the COVID‐19 pandemic. Population Studied: We purposefully sampled clinicians from both community and children's hospitals serving pediatric patients in the 6 U.S. states with the highest COVID‐19 hospitalization rates at the onset of the pandemic (NY, NJ, DC, MA, CT, LA). We recruited 2 participants from each hospital to interview (mix of administrators, physicians, and nurses). Principal Findings: We interviewed 24 participants from 12 hospitals and identified several themes [Table 1]. They described how hospital leaders rapidly developed policies to: 1) ensure adequate staff for surges of COVID‐19 patients, 2) provide adequate care spaces and supplies, 3) direct use of personal protective equipment, and 4) guide medical management of COVID‐19 patients. Hospital leaders optimized communication by conducting regular meetings to discuss the current state of the pandemic, hospital operations, and policy changes. In the setting of declining volumes of hospitalized children, clinicians newly provided care for hospitalized adults . This was facilitated by developing care teams supported by adult hospitalists, educational resources, and telehealth supports. Participants described negative impacts of the pandemic on clinicians' mental health, as well as helpful supports for clinician well‐being, including mental health resources, wellness activities and spaces, and housing. Finally, participants described experiences managing multisystem inflammatory syndrome in children including diagnostic uncertainty and evolving management for this novel disease. Table 1 : Theme Exemplary Quote Developing and evolving COVID‐related hospital policies "We have eight separate COVID related pathways. One for outpatient, one for ED, one for inpatient, and one for therapeutics. Pretty rigorous." Successful communication with clinicians and staff "One of the things that went really well was… daily town halls and transparency for the rapidly evolving situation." Newly providing care for hospitalized adults "They had what they called a super hospitalist, who was an adult hospitalist who would oversee…five or six different [mixed specialty care] teams and help out with some of the decision making." Organizing spaces for COVID‐19 patient care "As [the only freestanding] children's hospital [in the city], our role ended up being kind of a referral center for all the other centers to offload their pediatric patients." Conclusions: We identified several changes in inpatient pediatric care delivery and potential lessons learned during the COVID‐19 pandemic: 1) optimizing communication aided in rapidly changing hospital policies, 2) developing new team models and educational resources helped clinicians in newly caring for hospitalized adults, and 3) providing wellness resources was helpful for supporting clinicians' mental health. Implications for Policy or Practice: This study's findings will assist hospital leaders to plan for safe and high‐quality care for hospitalized children, in this ongoing pandemic and in future disaster planning. Primary Funding Source: Agency for Healthcare Research and Quality.